Dietary outcomes of overweight fathers and their children in the Healthy Dads, Healthy Kids community randomised controlled trial. Issue 4 (23rd February 2018) - Williams, A.; de Vlieger, N.; Young, M.; Jensen, M. E.; Burrows, T. L.; Morgan, P. J.; Collins, C. E.
Abstract: Background: Few studies have examined dietary intake changes following a weight loss intervention in fathers and the association between father–child dietary intakes. The present study aimed to: (i) evaluate the change in dietary intake in overweight fathers randomised to a family‐based lifestyle intervention [Healthy Dads Healthy Kids (HDHK)] versus controls and (ii) investigate whether an association exists between father–child dietary intakes. Methods: A secondary analysis was conducted of father–child baseline and 3‐month post‐intervention data ( n = 93) collected in the HDHK community randomised controlled trial. Intention‐to‐treat linear mixed models were used to assess dietary changes by group, time (baseline and 3‐month) and the group‐by‐time interaction. Cohens d was used to determine effect sizes. Results: Significant group‐by‐time effects (all P < 0.05) favouring fathers in the intervention group were identified for total daily energy intake (−1956 kJ, d = 0.74), total sugars (−45 g, d = 0.63), sodium (−414 mg, d = 0.58) and % energy from nutrient‐dense, core foods (+10.1%, d = 0.86), fruit (+2.4%, d = 0.71), vegetarian protein sources (+1.2%, d = 0.57), pre‐packed snacks (+1.7%, d = 0.58) and sugar‐sweetened beverages (−4.1%, d = 0.58). At baseline, positive correlations were observed between father–child intakes for a number of dietary variables, and significant correlations were observed between father–child change scores for % energy carbohydrate ( r = 0.35, P = 0.023), % energy from fruit ( r = 0.47, P = 0.002), vegetarian protein sources ( r = 0.46, P = 0.002) and frequency of consuming meals with vegetables ( r = 0.38, P = 0.012). Conclusions: The HDHK intervention successfully improved some aspects of father's dietary intakes compared to controls. The fathers' eating patterns also correlated with those of their children for several dietary variables. These novel data suggest that fathers can be targeted as agents of dietary change within obesity prevention and treatment programmes.